New rules of thumb maximizing energy efficiency in street lighting with discharge lamps: The general equations for lighting design. Issue 6 (2nd June 2016) - Peña-García, A.; Gómez-Lorente, D.; Espín, A.; Rabaza, O.
Abstract : New relationships between energy efficiency, illuminance uniformity, spacing and mounting height in public lighting installations were derived from the analysis of a large sample of outputs generated with a widely used software application for lighting design. These new relationships greatly facilitate the calculation of basic lighting installation parameters. The results obtained are also based on maximal energy efficiency and illuminance uniformity as a premise, which are not included in more conventional methods. However, these factors are crucial since they ensure the sustainability of the installations. This research formulated, applied and analysed these new equations. The results of this study highlight their usefulness in rapid planning and urban planning in developing countries or areas affected by natural disasters where engineering facilities and computer applications for this purpose are often unavailable.